The Effects of Store Environment and Merchandise to Customer Responses: an Empirical Study - Haryono, Richard I.; Sihombing, Sabrina O. (JDM (Jurnal Dinamika Manajemen), 2018)
This study aims to determine the relationship between store environments consisting of social cues, design cues, ambient gestures, and merchandise cues and their impact on cognitive and affective consumer evaluations of stores and merchandise that will influence approach behavior. The retail industry in Indonesia has increased inevitably. This development is predicted to continue to increase to 8% by 2018. As a result, stores are competing to offer new and unique experiences for both cognitive and affective customers. Over the past decade, similar research has rarely been done. In addition, item cues variables are also rarely mentioned in previous studies. Therefore, this study aims to explain more about merchandise cues. The basis of this research is quantitative method, using descriptive research type with research object Foodmart Primo Maxxbox Lippo Village. The sample size involved 200 respondents selected by applying purposive sampling. After data collected, the data were analyzed by using structural equation modeling (SEM). There are three out of 12 hypotheses that were not supported in this study. The three hypotheses are the relationship between ambient cues with consumers’ cognitive evaluation of the store, and no relationship between consumer cognitive evaluation and approach behavior. Theoretical and managerial implications and suggestions for further research are also discussed in this study.This study aims to determine the relationship between store environments consisting of social cues, design cues, ambient gestures, and merchandise cues and their impact on cognitive and affective consumer evaluations of stores and merchandise that will influence approach behavior. The retail industry in Indonesia has increased inevitably. This development is predicted to continue to increase to 8% by 2018. As a result, stores are competing to offer new and unique experiences for both cognitive and affective customers. Over the past decade, similar research has rarely been done. In addition, item cues variables are also rarely mentioned in previous studies. Therefore, this study aims to explain more about merchandise cues. The basis of this research is quantitative method, using descriptive research type with research object Foodmart Primo Maxxbox Lippo Village. The sample size involved 200 respondents selected by applying purposive sampling. After data collected, the data were analyzed by using structural equation modeling (SEM). There are three out of 12 hypotheses that were not supported in this study. The three hypotheses are the relationship between ambient cues with consumers’ cognitive evaluation of the store, and no relationship between consumer cognitive evaluation and approach behavior. Theoretical and managerial implications and suggestions for further research are also discussed in this study.